A Community Partnership for Home Delivery of Food Boxes to COVID-19 Quarantined and Isolated Families. Issue 1 (2nd January 2021) - English, Emily; Long, Christopher R.; Langston, Krista; Faitak, Bonnie; Brown, April L.; Echegoyen, Amanda; Gardner, Joel; Cowan, Casey; Rambo, Debbie; Perritt, Brenda; Laubenstein, Barb; Snyder, Alyssa; et al.
ABSTRACT: Latinx and Marshallese populations experienced significant COVID-19 disparities in Arkansas, as well as high rates of food insecurity. This case study describes a partnership to rapidly deliver food to isolated and quarantined individuals with COVID-19. It focuses on the project's initial three weeks (June 19–July 2, 2020) of operation in which 531 home deliveries of food boxes were made to 2, 192 unique individuals in 373 unique households. This community partnership was possible because of existing relationships established prior to the pandemic and leveraged to rapidly reach and respond to acute need in the community.